2016
DOI: 10.18632/oncotarget.13036
|View full text |Cite
|
Sign up to set email alerts
|

TRIM71 suppresses tumorigenesis via modulation of Lin28B-let-7-HMGA2 signaling

Abstract: TRIM71 (tripartite motif-containing 71) belongs to the TRIM-NHL protein family, which plays a conserved role in regulating early development and differentiation. However, the molecular functions of TRIM71 have remained largely unknown. Here, we explored the role of TRIM71 together with modulation of Lin28B-let-7-HMGA2 (high-mobility group AT-hook 2) signaling in tumorigenesis. TRIM71 overexpression opposed Lin28B-induced transformation in primary cells and inhibited tumor formation in a mouse model. Specific k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
(81 reference statements)
2
18
0
Order By: Relevance
“…The RING motif of TRIM71 is essential for target protein ubiquitin-dependent degradation or stabilization. TRIM71 acts as a specific E3 ubiquitin ligase, downregulates the expression of AGO proteins [ 14 , 15 ] and the RNA-induced silencing complex components, and promotes the expression of let-7 downstream target proteins [ 16 18 ]. Moreover, TRIM71 has been shown to stabilize Shc SH2-binding protein 1 (SHCBP1), a component of fibroblast growth factor (FGF) signaling, via ubiquitination and to enhance FGF signaling in neuronal progenitor cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RING motif of TRIM71 is essential for target protein ubiquitin-dependent degradation or stabilization. TRIM71 acts as a specific E3 ubiquitin ligase, downregulates the expression of AGO proteins [ 14 , 15 ] and the RNA-induced silencing complex components, and promotes the expression of let-7 downstream target proteins [ 16 18 ]. Moreover, TRIM71 has been shown to stabilize Shc SH2-binding protein 1 (SHCBP1), a component of fibroblast growth factor (FGF) signaling, via ubiquitination and to enhance FGF signaling in neuronal progenitor cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although we have previously reported that the protein level of Lin28A had decreases in PCAF-transfected cells [ 26 ], Lin28B was not substantially changed at the protein level (data not shown). Both Lin28A and Lin28B interact with PCAF via their CSD, and let-7 binds to the 3’UTR of both Lin28 paralogs, thereby repressing Lin28 translation in a negative feedback loop; however, TRIM71, a specific E3 ubiquitin ligase, negatively regulates Lin28B (but not Lin28A) protein levels by ubiquitinating its C-terminal unique region, which is absent in the Lin28A paralog [ 24 , 25 ]. It might be interesting to study whether the acetylation of Lin28B by PCAF affects the poly-ubiquitination of Lin28B at the C-terminal region and may alter its stability.…”
Section: Discussionmentioning
confidence: 99%
“…Protein acetylation is known to participate in regulating multiple cellular processes in normal and cancer cells [ 21 23 ]. As a bona fide cancer-related protein, Lin28B is subject to polyubiquitination that leads to the enhancement of let-7 biogenesis [ 24 , 25 ]. However, whether the acetylation of Lin28B affects the let-7 biogenesis involved in tumorigenesis is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although Lin28B upregulation by downregulation of let-7-5p family was simulated in Figure 5B, Lin28B could further repress let-7-5p family expression via human ubiquitin ligase TRIM71 [123]. On the other hand, super-downregulation of let-7-5p would increase TRIM71 ( Figure 5C) and TRIM71 overexpression opposed Lin28B-inducing transformation [124]. Since downregulation of miR-203a-3p and let-7-5p family would increase TRIM71 ( Figure 5C), Figure 5B).…”
Section: Stage I-ii Simulation Of Nsclc and Network Analysismentioning
confidence: 95%